2020
DOI: 10.32582/aa.61.2.1
|View full text |Cite
|
Sign up to set email alerts
|

Non-indigenous cephalopods in the Mediterranean Sea

Abstract: The present review critically assesses the records of cephalopods that have entered the Mediterranean Sea in the last few decades. It includes 13 species, namely Sepia dollfusi, Stoloteuthis leucoptera, Sepioteuthis lessoniana, Architeuthis dux, Cranchia scabra, Taonius pavo, Megalocranchia sp., Teuthowenia megalops, Cycloteuthis sirventi, Taningia danae, Octopus cyanea, Amphioctopus sp. and Tremoctopus gracilis. The presence of Sepia pharaonis needs to be confirmed, whereas that of Sepia gibba and Spirula spi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…This study once again confirms that errors/misidentifications are common in public repositories [ 7 , 53 ], probably because there are not many and easily applicable taxonomic characters used in the field to distinguish them, especially separating T. violaceus and T. gracilis . These discrepancies between the morphological and molecular identification, suggest adopting a more precautionary approach when reassigning old records to a different species based solely on the colour patterns deducted from drawings/photos [ 8 , 9 , 10 ] or extending the geographical range of species (e.g., T. gracilis within the Mediterranean Sea), based solely on sporadic observations, described in conference papers almost impossible to find for consultation [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This study once again confirms that errors/misidentifications are common in public repositories [ 7 , 53 ], probably because there are not many and easily applicable taxonomic characters used in the field to distinguish them, especially separating T. violaceus and T. gracilis . These discrepancies between the morphological and molecular identification, suggest adopting a more precautionary approach when reassigning old records to a different species based solely on the colour patterns deducted from drawings/photos [ 8 , 9 , 10 ] or extending the geographical range of species (e.g., T. gracilis within the Mediterranean Sea), based solely on sporadic observations, described in conference papers almost impossible to find for consultation [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…The difficulty in separating these taxa, as well as the paucity of molecular data, could cause several errors in identifications, especially involving T. violaceus and T. gracilis , as exemplified by the records of these two species outside their known geographical limits [ 7 ]. For instance, in the Mediterranean Sea, in the past, T. violaceus was the only member of the genus known to live in the area, while nowadays it is reported that two species of the genus Tremoctopus occur in the Mediterranean Sea, i.e., T. violaceus as the native species and T. gracilis as an alien species probably arriving in the Mediterranean due to human-mediated transfer or with Lessepsian migrations [ 8 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides negative effects such as the reduction in native biodiversity and ecosystem shifts, there might also be benefits from NIS, such as the replacement of lost ecological functions and the strengthening of biogenic complexity (Kleitou et al 2021). A recent study describes 13 non-indigenous cephalopod species for the Mediterranean Sea, which entered the region over the last few decades, most likely by the following three different routes: the natural pathway Strait of Gibraltar, the human-constructed pathway Suez Canal or through other anthropogenic pathways like shipping (Bello et al 2020). Consequently, cephalopods should also be considered in the NIS assessment within the MSFD (D2).…”
Section: Introductionmentioning
confidence: 99%